Övervakning av ston i sen dräktighet genom transrektal ultraljudsundersökning av placentan - Staaf, Cecilia (2008)
Abortion during late gestation is often caused by placental dysfunction such as placentitis. To prevent this from happening the placenta can be monitored pre partum so treatment can be started at an early stage. Methods for monitoring the placenta include hormonal monitoring, presence of clinical signs of placental dysfunction and ultrasonographic evaluation of the fetus and the placenta. Transrectal ultrasonography provides a very good image of the caudal portion of the allantochorion where an ascending placentitis normally establishes.